The development of crop decision trees for climate risk management - Kwang-Hyung, Kim; Barlis, Angelica; Palao, Leo Kris; Mienmany, Bandit; Imbach, Pablo; Swaans, Cornelis P.M. (DeRISK SE Asia, 2022)
This brief summarizes how location-specific crop decision trees are developed from their basic structure, starting from a top-down approach combined with local-level validation to ensure relevance and applicability at the farm level.